Evaluation of Health-related Quality of Life Improvement in Patients Undergoing Spine Versus Adult Reconstructive Surgery. Issue 18 (15th September 2020) - Varlotta, Christopher; Fernandez, Laviel; Manning, Jordan; Wang, Erik; Bendo, John; Fischer, Charla; Slover, James; Schwarzkopf, Ran; Davidovitch, Roy; Zuckerman, Joseph; Bosco, Joseph; Protopsaltis, Themistocles; et al.
Abstract : Study Design: Retrospective analysis of outcomes in single-level spine and primary hip and knee arthroplasty patients. Objective: The aim of this study was to compare baseline and postoperative outcomes in patients undergoing spine surgery procedures with total hip arthroplasty (THA) and total knee arthroplasty (TKA) to further define outcomes in orthopedic surgery. Summary of Background Data: Computer-adaptive Patient Reported Outcome Information System (PROMIS) allows for standardized assessment of the health-related quality of life across different disease states. Methods: Patients who underwent spine surgery (anterior cervical discectomy and fusion, cervical disc replacement, lumbar laminectomy, microscopic lumbar discectomy, transforaminal lumbar interbody fusion or adult reconstruction surgery [THA, TKA]) were grouped. Mean Charlson Comorbidity Index (CCI), Baseline (BL), and 6-month PROMIS scores of physical function, pain interference, and pain intensity were determined. Paired t tests compared differences in CCI, BL, 6 months, and change in PROMIS scores for spine and adult reconstruction procedures. Results: A total of 304 spine surgery patients (age = 58.1 ± 15.6; 42.9% female) and 347 adult reconstruction patients (age = 62.9 ± 11.8; 54.1% Female) were compared. Spine surgery groups had more disability and pain at baseline than adult reconstruction patients according to physical function ([21.0, 22.2, 9.07, 12.6, 10.4] vs. [35.8, 35.0], respectively, P  < 0.01), pain interference ([80.1, 74.1, 89.6, 92.5, 90.6] vs. [64.0, 63.9], respectively, P  < 0.01), and pain intensity ([53.0, 53.1, 58.3, 58.5, 56.1] vs. [53.4, 53.8], respectively, P  < 0.01). At 6 months, spine surgery patients remained more disabled and had more pain compared to adult reconstruction patients. Over the 6-month timespan, spine patients experienced greater improvements than adult reconstruction patients in terms of physical function ([+8.7, +22.2, +9.7, +12.9, +12.1] vs. [+5.3, +3.9], respectively, P  < 0.01) and pain interference scores ([−15.4, −28.1, −14.7, −13.1, −12.3] vs. [−8.3, −6.0], respectively, P  < 0.01). Conclusion: Spinal surgery patients had lower BL and 6-month PROMIS scores, but greater relative improvement in PROMIS scores compared to adult reconstruction patients. Level of Evidence: 3 Abstract : Retrospective analysis of outcomes with the utilization of PROMIS in patients undergoing single-level spine procedures and total hip arthroplasty (THA) and total knee arthroplasty (TKA). Spine surgery patients demonstrated greater baseline and 6-month disability, but greater overall improvement in disability and pain scores at 6 months compared to THA and TKA patients.